2019
DOI: 10.1037/ppm0000165
|View full text |Cite
|
Sign up to set email alerts
|

Romantic relationship-oriented Facebook activities and the satisfaction of belonging needs.

Abstract: Facebook plays a role in the development and maintenance of romantic relationships. Theoretically, individuals are motivated to use Facebook in their relationships to increase feelings of belongingness, which is a fundamental human need. Yet, past studies have neither examined the perceptions of Facebook's influence on increasing closeness in romantic relationships, nor simultaneously examined a wide range of Facebook behaviors that involve romantic partners. Using a belongingness/connection framework, 2 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 50 publications
(89 reference statements)
1
38
0
Order By: Relevance
“…Individuals can also publicly display their current or anticipated romantic relationship on Facebook by having a dyadic profile picture or sharing pictures of activities on their own profiles. Studies have shown how common this behavior is and its links to relationship satisfaction (Saslow, Muise, Impett, & Dubin, 2013; Seidman, Langlais, & Havens, 2017) and commitment (Toma & Choi, 2015). Individuals can also publicly display their relationships through comments or posts on the Facebook content of current or potential romantic partners.…”
Section: Romantic Relationship–oriented Facebook Behaviorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Individuals can also publicly display their current or anticipated romantic relationship on Facebook by having a dyadic profile picture or sharing pictures of activities on their own profiles. Studies have shown how common this behavior is and its links to relationship satisfaction (Saslow, Muise, Impett, & Dubin, 2013; Seidman, Langlais, & Havens, 2017) and commitment (Toma & Choi, 2015). Individuals can also publicly display their relationships through comments or posts on the Facebook content of current or potential romantic partners.…”
Section: Romantic Relationship–oriented Facebook Behaviorsmentioning
confidence: 99%
“…Individuals can also publicly display their relationships through comments or posts on the Facebook content of current or potential romantic partners. This behavior is common and linked to increased relationship quality of romantic relationships (Saslow et al, 2013; Seidman et al, 2017; Toma & Choi, 2015). However, individuals may overshare information on Facebook or share information that is embarrassing or inappropriate.…”
Section: Romantic Relationship–oriented Facebook Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 However, because individuals tend to post especially attractive versions of themselves online, 15 it is possible that those in unhappy relationships continue to post unrealistic couple photographs on social media as a compensatory mechanism or a self-presentation strategy to appear happier in their relationships to others. 12,16 Because social learning theories state that individuals construct their relationship views as a result of observing models or 'scripts' around them, 17,18 it is important to understand what relationship portrayals adolescents witness on social media platforms. Furthermore, we need to know whether adolescents feel influenced by such relationship portrayals online, and whether this influence can construct or alter their views on what a relationship should look like.…”
Section: Introductionmentioning
confidence: 99%